1991
DOI: 10.3801/iafss.fss.3-291
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Compartment Fires With Overhead Forced Ventilation

Abstract: Compartment fire data with either no ventilation or forced overhead ventilation are successfully modeled as well-stirred fire environments rather than two-layer fire environments, The extinction of flames is predicted using the limiting oxygen index concept linked with a well-stirred model of the fire environment. While the fire environment in compartments with overhead ventilation is quite different than naturally-ventilated fires or fires ventilated from floor level, a temperature model previously developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 7 publications
(12 reference statements)
1
16
0
Order By: Relevance
“…A similar behavior has been observed for naturally ventilated compartments with small openings (low natural ventilated conditions) [4,5]. From that moment on, the pool fire burn; in a vitiated atmosphere due to the presence of combustion products, which most often leads to extinction of the flame as soon as the oxygen concentration in the gaseous mixture drops below a critical value between 11% and 15% expressed in terms of mole fraction [3,6,7,8]. A recent study by Sugawa et A1 [5], dealing with a small-sized room (3 m long, 2 m wide and 0.6 m high) which had in its center a pool fire (methanol) of 0.30 m in diameter, has shown a behavior of the flame that is not common during the phase preceding fire extinction.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…A similar behavior has been observed for naturally ventilated compartments with small openings (low natural ventilated conditions) [4,5]. From that moment on, the pool fire burn; in a vitiated atmosphere due to the presence of combustion products, which most often leads to extinction of the flame as soon as the oxygen concentration in the gaseous mixture drops below a critical value between 11% and 15% expressed in terms of mole fraction [3,6,7,8]. A recent study by Sugawa et A1 [5], dealing with a small-sized room (3 m long, 2 m wide and 0.6 m high) which had in its center a pool fire (methanol) of 0.30 m in diameter, has shown a behavior of the flame that is not common during the phase preceding fire extinction.…”
Section: Introductionmentioning
confidence: 60%
“…Under these under-ventilated conditions, the hot upper layer progressively invades all the compartment and a single hot layer is formed from a mixture of air and combustion products. It is then said that the fire is controlled by ventilation and the room on fire has a well-stirred compartment behavior as described by Beyler [3]. A similar behavior has been observed for naturally ventilated compartments with small openings (low natural ventilated conditions) [4,5].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…These forces yield a substantial recirculation flow that acts to create a uniform, well-mixed environment. Beyler [7] and Peatross and Beyler [8] have identified that the species concentrations are generally more uniform than temperature because species are not lost to compartment boundaries, while thermal energy is lost to these surfaces. Because of the heat loss dynamics, temperature non-uniformities are present.…”
Section: Fssim Implementationmentioning
confidence: 99%
“…The main applications for which research has been conducted are the use of positive pressure ventilation (PPV) techniques for smoke control [1], the interest of forced ventilated fire scenarios [14,15] or the HVAC (heat ventilation air conditioning) system in buildings [2].…”
Section: Introductionmentioning
confidence: 99%